Dengvaxia®: the World's First Dengue Vaccine - He, Siyi; Sauer , Jeffrey; Fanous, Juliana; Anchuri, Kavya; Lahlou, Hicham; Legrand, Alice; Labasi-Sammartino, Catherine (McGill Journal of Global Health, 2017)
Dengue fever is considered a Neglected Tropical Disease (NTD), as it both affects predominantly resource-limited countries and highlights the need for increased research and development (R&D) (1). The situation has become critical given that transmission of dengue has increased in both fre- quency and magnitude, and has expanded to new areas. However, over the last two decades, den- gue R&D has grown extensively, particularly in the vaccine division of the pharmaceutical company Sanofi, which has led to the development of the world’s first dengue vaccine: Dengvaxia®. Con- cerns have now surfaced regarding the vaccine’s efficiency, specifically amongst children younger than 9 years of age, and in low-transmission areas. Therefore, the creation of Dengvaxia® is not the final step towards the eradication of dengue. R&D must not only continuously seek an improved version of Dengvaxia®, but should also consider other dengue vaccine candidates, and improve distribution of the vaccine in all affected countries.